Dynamic patterns of mechanical stimulation co-localise with growth and cell proliferation during morphogenesis in the avian embryonic knee joint - Prendergast, Patrick; Murphy, Paula (University of Edinburgh (datashare), 2011)
Muscle contractions begin in early embryonic life, generating forces that regulate the correct formation of the skeleton. In this paper we test the hypothesis that the biophysical stimulation generated by muscle forces may be a causative factor for the changes in shape of the knee joint as it grows. We do this by predicting the spatial and temporal patterns of biophysical stimuli, where cell proliferation and rudiment shape changes occur within the emerging tissues of the joint over time. We used optical projection tomography (OPT) to create anatomically accurate finite element models of the embryonic knee at three time points (stages) of development. OPT was also used to locate muscle attachment sites and AFM was used to determine material properties. An association was found between the emergence of joint shape, cell proliferation and the pattern of biophysical stimuli generated by embryonic muscle contractions. Elevated rates of growth and cell proliferation in the medial condyle were found to co-localise with elevated patterns of biophysical stimuli including maximum principal stresses and fluid flow, throughout the time period studied, indicating that cartilage growth and chondrocyte proliferation in the epiphysis is potentially related to local patterns of biophysical stimuli. The development of the patella and articular cartilages, which is known to be affected by in ovo immobilisation, could be contributed to by specific patterns of fluid flow, pore pressure and stress in the joint interzone. This suggests that both cartilage growth and in the embryonic joint is regulated by specific patterns of biophysical stimuli and that these stimuli are needed for the correct development of the joint.
Roles of Skeletal Muscle in Organ Development
PUBLISHED
Keywords: Bioengineering; tissue differentiation; Next Generation Medical Devices